Effectiveness of the rural transitions nurse program for Veterans: A multicenter implementation study. Issue 3 (4th March 2022) - Gilmartin, Heather M.; Warsavage, Theodore; Hines, Anne; Leonard, Chelsea; Kelley, Lynette; Wills, Ashlea; Gaskin, David; Ujano‐De Motta, Lexus; Connelly, Brigid; Plomondon, Mary E.; Yang, Fan; Kaboli, Peter; et al.
Abstract: Background: Veterans are often transferred from rural areas to urban VA Medical Centers for care. The transition from hospital to home is vulnerable to postdischarge adverse events. Objective: To evaluate the effectiveness of the rural Transitions Nurse Program (TNP). Design, Setting, and Participants: National hybrid‐effectiveness‐implementation study, within site propensity‐matched cohort in 11 urban VA hospitals. 3001 Veterans were enrolled in TNP from April 2017 to September 2019, and 6002 matched controls. Intervention and Outcomes: The intervention was led by a transitions nurse who assessed discharge readiness, provided postdischarge communication with primary care providers (PCPs), and called the Veteran within 72 h of discharge home to assess needs, and encourage follow‐up appointment attendance. Controls received usual care. The primary outcomes were PCP visits within 14 days of discharge and all‐cause 30‐day readmissions. Secondary outcomes were 30‐day emergency department (ED) visits and 30‐day mortality. Patients were matched by length of stay, prior hospitalizations and PCP visits, urban/rural status, and 32 Elixhauser comorbidities. Results: The 3001 Veterans enrolled in TNP were more likely to see their PCP within 14 days of discharge than 6002 matched controls (odds ratio = 2.24, 95% confidence interval [CI] = 2.05–2.45). TNP enrollment was not associated with reduced 30‐day ED visits or readmissions but was associated with reduced 30‐day mortality (hazard ratio = 0.33, 95% CI = 0.21–0.53). PCP and ED visits did not have a significant mediating effect on outcomes. The observational design, potential selection bias, and unmeasurable confounders limit causal inference. Conclusions: TNP was associated with increased postdischarge follow‐up and a mortality reduction. Further investigation to understand the reduction in mortality is needed.